Efficacy of 600 Î¼g Misoprostol compare to 400 Î¼g Misoprostol orally for expulsion of conception mass on pregnancy failure under twenty two weeks of gestational age - Rosa, Rahmedi (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To evaluate the efficacy and adverse effect of misoprostol in pregnancy termination under 22 weeks of gestation with dosage 400 Î¼g, in comparison to 600 Î¼g. Method: The research was performed in Obstetric and Gynecology Division in Dr. Cipto Mangunkusumo General Hospital to 70 subjects which were chosen with consecutive sampling, divided into two groups with block randomization and double blind. Group A received 400 Î¼g of misoprostol every 6 hours while group B received 600 Î¼g of misoprostol every 6 hours for a maximum of 2 days. Each group was evaluated for the time it took to reach complete abortion and for the adverse effects, consisting of abdominal cramping, bleeding, vomiting, and diarrhea. Result: Success rate for termination with misoprostol 400 Î¼g and 600 Î¼g were 88.5% and 91.4%, with no statistical difference found (p=1.000). There was no difference in the time for reaching complete abortion between two dosages (p=0.701) with a mean of 22 Â± 8 hours. Adverse effects were found more frequent and more severe in the group consuming 600 Î¼g of misoprostol compared to the group receiving 400 Î¼g of misoprostol. Conclusion: Four hundred micrograms of misoprostol every six hour is recommended for termination of pregnancy under 22 weeks of gestational age, without statistical difference in efficacy, but with lower adverse effects. [Indones J Obstet Gynecol 2010; 34-2: 59-63] Keywords: misoprostol, pregnancy failure, dosage, efficacy, adverse effect